Pemilu dan Demokrasi Telaah terhadap Prasyarat Normatif Pemilu - Sri Hastuti Puspitasari (Fakultas Hukum Universitas Islam Indonesia, 2004)
Prerequisite of normative democratic election is crucial, it is needed to measure the content of democracy it seif, but if the prerequisite is not accompanied by the strong commitment from the institution and the voters for streng then the other democratic principles, the general election is not perfect. In the other hand, the election handled would be defective.